Pollius Felix and the Porticus Liviae (Statius' Silvae 2.2.31). - Liney, Nicolas (Symbolae Osloenses, 2021)
This article considers the tensions between private dwelling and public city space in architecture and rhetoric in imperial Rome, particularly as they appear in Statius' Silvae 2.2, an ecphrastic poem on a seaside villa. When Statius describes his patron's porticus as "the size of a city" (urbis opus, 2.2.31), he is alluding to an Augustan monument, the Porticus Liviae described in Ovid's Fasti (6.637–648). By so doing, Statius deconstructs the traditional urbs/domus familiar from Roman moralizing discourse, a binary that had been further complicated by Nero's Domus Aurea, a recent travesty in Flavian cultural memory. We are prompted to question Statius' representation of Pollius, as ktistic city-founder, indulgent tyrant – and as potential foil for the emperor Domitian.